Impact of New National Education Policy among School Students - KP, Krishnaveni; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
To realize the potential of education, Indian countries need to tackle the four tensions and establish an education system that prepares all students for a productive and successful future. Such a system would be modern and flexible and would nurture a culture of excellence and creativity in learning. It also would leverage disruptive technologies and adopt modern approaches so it can offer young people the skills they need to define their trajectories in life and adapt to local, national, and global changes. Finally, it would be based on a shared national vision and would connect with the overall development goals of the country. All of society would be responsible for ensuring its success. To establish such a system, India countries need to adopt a new framework for education one that includes a concerted push for learning, a wide-reaching pull for skills, and a new pact for education. This paper discusses the actions needed to implement this framework. It sheds light on the dimensions of the crisis and proposes a way forward that is well aligned with the push, pull, and pact framework described here. It further reinforces the importance of all stakeholders working together to promote a focus on learning and skills. Research has established firmly that stress and anxiety reduce performance effectiveness. It has the capability of multiplying the human intellect and has tremendous educational implications. Hence the problem selected for the present investigation has been stated as follows, “Impact of new National Education Policy among School Students.” The research mainly gives us good opening to see inside the problem which has been selected for the present investigation. It also gives the investigator to give suggestions upon the derived findings. The findings may also be forwarded to the concerned authorities of the Government with all the evidences so that the Government can be implement the remedies to the problems at the earliest which gives the subjects a relief and benefit. The title of the study has been highlighted as, “Impact of new National Education Policy among School Students.” How to cite this article:  Krishnaveni KP, Selvakumar YS. Impact of New National Education Policy among School Students. J Adv Res Eng & Edu 2022; 7(2): 1-4. DOI: https://doi.org/10.24321/2456.4370.202202